Protein and RNA dynamical fingerprinting - Katherine A. Niessen (Nature Portfolio, 2019)
The characterization of biomacromolecule structural vibrations has been impeded by a broad continuous vibrational density of states obscuring molecule specific vibrations. A terahertz microscopy system using polarization control produces signatures to dynamically fingerprint proteins and a RNA G-quadruplex.